Particulate emission inventory and trends in ambient particulate matter concentrations in the Czech Republic between 1993 and 1999 - Branis, Martin (Environmental monitoring and assessment, 2003)
Trends in total suspended particulates (TSP) emission inventories were compared with ambient TSP concentrations during the period of 1993-1999 in the Czech Republic. The TSP annual emission decreased within the period of observation from 441,300 to 67,000 of metric tonnes (by 85%). During the same period a less pronounced downward trend from 80.3 microg m(-3) to 31.5 microg m(-3) (decrease by 61%) was noted also for the ambient TSP annual average. Difference between the two air quality indicators seems to indicate that changes in TSP emission inventories from year to year are being to some extent overestimated. Monthly ambient particulate concentrations did not respond to overall drop in emissions proportionately but were closely associated with monthly mean temperatures. While in the winter the correlation between ambient TSP and temperature was negative, in summer the correlation between the two variables was positive. In spring and autumn there was no clear correlation between temperature and ambient particulate pollution. The improvement of air quality in the Czech Republic since the economical and political transformation in 1990s is substantial when demonstrated by emission figures, however, true state of particulate pollution expressed by ambient levels requires further attention.
Keywords: životní prostředí; Politics; Environmental Monitoring; politika; Environment; látky znečišťující vzduch; znečištění ovzduší; monitorování životního prostředí; roční období; Humans; Česká republika; lidé; Air Pollution; Air Pollutants; Particle Size; Seasons; Czech Republic; velikost částic